2008
DOI: 10.1007/s00426-008-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spatial frequency content on parameters of eye movements

Abstract: Two experiments were conducted to examine the inXuence of the spatial frequency content of natural images on saccadic size and Wxation duration. In the Wrst experiment 10 pictures of natural textures were low-pass Wltered (0.04-0.76 cycles/deg) and high-pass Wltered (1.91-19.56 cycles/deg) and presented with the unWltered originals in random order, each for 10 s, to 18 participants, with the instruction to inspect them in order to Wnd a suitable name. The participants' eye movements were recorded. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
4
10
1
Order By: Relevance
“…First of all, consistent with prior findings (Groner et al, 2008;Loschky et al, 2005;Mannan et al, 1995), we found that across all three experiments, fixation durations were lengthened when scenes were band-pass filtered for spatial frequencies. More important, because the filtered scene information was presented during the saccade prior to the critical fixation and could not be predicted in advance, we can infer that the duration of the critical fixation was influenced by processing of the filtered scene information that occurred during the critical fixation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First of all, consistent with prior findings (Groner et al, 2008;Loschky et al, 2005;Mannan et al, 1995), we found that across all three experiments, fixation durations were lengthened when scenes were band-pass filtered for spatial frequencies. More important, because the filtered scene information was presented during the saccade prior to the critical fixation and could not be predicted in advance, we can infer that the duration of the critical fixation was influenced by processing of the filtered scene information that occurred during the critical fixation.…”
Section: Discussionsupporting
confidence: 90%
“…For example, it has been shown that restricting or degrading the availability of stimulus information has an effect on fixation durations (Groner, Groner & von Mühlenen, 2008;Loftus, 1985;Loschky, McConkie, Yang & Miller, 2005;Mannan, Ruddock & Wooding, 1995;Parkhurst, Culurciello & Niebur, 2000). More specifically, when spatial frequency information is filtered from scenes (e.g., using a band-pass filter), fixation durations tend to increase.…”
mentioning
confidence: 99%
“…The spatial frequencies of an image affect the fixation durations and saccade amplitudes so that low frequencies elicit larger saccades associated with shorter fixation durations and high frequencies elicit smaller saccades associated with longer fixation durations (Groner et al, 2008). The medians for the saccade amplitudes seemed to be distributed similarly among different visualizations in the current study, Figure 7.…”
Section: Discussionsupporting
confidence: 48%
“…It nevertheless clearly affects fixation frequency and saccade length. As shown previously with texture stimuli (Groner et al, 2008), HP images produced shorter saccades than LP images, suggesting that visible content in the periphery is necessary for saccades to that region. In other words, saccades seem not to be directed to image areas for which no information is available even if content seems likely to be there given normal scene structure (Ossandón et al, 2011).…”
Section: Discussionmentioning
confidence: 53%
“…Such low cutoff changes eye-movement parameters (Groner, Groner, & von Mühlenen, 2008) but preserves clear visual content in both LP and HP images ( Figure 4A). To avoid identifying differences in exploration due only to differences in overall luminance between LP and HP images, the HP version preserved the mean luminance of the original images.…”
Section: Stimulimentioning
confidence: 96%